Analisis Waktu dan Biaya Berdasarkan Acuan Produktivitas Lapangan Menggunakan Metode Estimasi Biaya Aktual - Rahmat Tri Prasetya; Totok Yulianto; Meriana Wahyu Nugroho; Titin Sundari (Pusat riset dan Inovasi Nasional, 2023)
The improvement of the Cukir-Jombang road section requires heavy equipment. There is an increase in the road section at the STA. 0+000-STA. 0+936 and STA. 1+912 – STA. 2+790. In order to obtain cost and time efficiency, it is necessary to analyze the productivity of heavy equipment. This study uses the field productivity method with the aim of knowing the maximum productivity of heavy equipment and asphalt costs starting from STA 0+000 to completion. The results of this study obtained the rental time of heavy equipment for 8 hours with the number of each heavy equipment Asphalt Finisher 2 units, Dump Trucks 20 units, Tandem Roller 3 units, Pneumatic Tire Roller 2 units, Asphalt Sprayer 1 unit. Meanwhile, the cost of renting heavy equipment is IDR 4,180,000.00 for Asphalt Finisher, IDR 34,200,000 for Dump Trucks, IDR 5,700,000.00 for Tandem Rollers, IDR 3,800,000 for Pneumatic Tire Rollers, and IDR 532,000 for Asphalt Sprayers.